The Role of SMEs in Export Promotion: Evidence from the Manufacturing Industry of Ghana - Anning, Lucy; Haisu, Wang (Journal of Asian Business Strategy, 2020)
The study sets to investigate the complex nexus of why the majority of SMEs from the manufacturing industry of Ghana decide to focus on the domestic market, while few choose to sell a proportion of their goods abroad (thus engage in export activities), even though they face and operate in similar market conditions. While a huge variety of clarifications to this issue exists in current writing analyzing the export behavior of SMEs organizations, these clarifications anyway are uncertain and confined in geographic extension along these lines created nations setting. Methodologically, the study utilizes both quantitative and qualitative techniques in addressing the phenomenon. The quantitative method involves the logit probability regression analysis while the qualitative analysis is based on a systematic content review of data amidst descriptive statistics. Overall, firm size, sub sector, workforce education levels, government inclusion, financial availability and participation in international and domestic business networks are found to be the key drivers explaining why some manufacturing SMEs from Ghana choose to export, while majority of others remained focused on the domestic market. In light of the discoveries it is presumed that SME proprietor administrators in Ghana trying to fare ought to put resources into the improvement of both local and global systems as a methods for improving their entrance to worldwide markets. From a policy point of view, an intriguing suggestion for the legislature of Ghana to give further help in a bid to encourage the actions of industrial associations in Ghana is profoundly underscored.